Effects of tether dimensions and seasonal variations on the performance of bare electrodynamic tethers. (1st May 2022) - Liang, Fuwen; Xie, Kan; Miao, Long; Tian, Feng; Song, Jiahui; Bai, Song; Akintade, Rebeccah O.; Wang, Ningfei
Highlights: Lorentz force and atmospheric drag are both important in EDT deorbit. Large length/width cannot effectively increase EDT performance. Effect of seasonal variations should be considered in advanced simulations. Effect of electron density changed with seasonal variations is more pronounced. Abstract: An electrodynamic tether (EDT) system that utilizes geomagnetic field and space plasma in the Earth's ionosphere to generate thrust has been studied. In this study, a bare EDT deorbiting model, including the realistic discharge characteristics of a hollow cathode, is introduced. (1) The effect of tether dimensions on the deorbiting performance of the EDT system was systematically studied using this model. A longer and wider tape cannot always effectively promote the EDT performance. It significantly increases the mass of the system and thus the launch cost. A tape with a length of 18 km and width of 1.5 cm was chosen as optimal in this study. (2) The effect of seasonal variations on the EDT performance was studied using the model. The four seasons in 2005 were selected as reference starting dates for the Earth's ionosphere and atmospheric density models. Spring was recommended as the starting date for a better deorbiting performance of the EDT. The effect of seasonal variations on the different position distributions of high-power current in the tether was observed in the numerical simulations.